Réponses

  • Utilisateur Brainly
2014-03-20T06:39:42+01:00
{ mx+z=1      
{x+y+mz=2      
{-x+my+1=0 

Méthode : on effectue une disjonction de cas

1er cas : m=0
{ z=1      
{x+y=2      
{-x=0-1
donc S={(1;1;1)}

2ème cas : m=-2
donc S={(-1;1;-1)}

3ème cas : m=-1
donc S={(-2;3;-1)}

4ème cas : m=1
donc S={(2;1;-1)}

5ème cas : m ≠ -2 ; m ≠ -1 ; m ≠ 0 ; m ≠ 1
{ mx+z=1      
{x+y+mz=2      
{-x+my+1=0 
donc
{ mx+z=1      
{x+y+mz=2      
{(m+1)y+mz=1
donc
{ x=(1-z)/m      
{x+y+mz=2     
{y=(1-mz)/(m+1)   
donc
{ x=(1-z)/m      
{(1-z)/m+(1-mz)/(m+1)+mz=2     
{y=(1-mz)/(m+1)   
donc
S={((m²-2m-1)/(m³-m-1); (-m²+m-1)/(m³-m-1); (2m²-1)/(m³-m-1)}